(3NHQ GdjghO hGdfUGQis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOK ef hKb Hg hScf Zdi bhdg eY ETgGQ GdMOjK ai Pdc GdhbJ Cfg MVf ai ehba ef GdehGba GdOgQ s
(3BNQgG (B:s
(3abGd eGPG Gdbhdhf bGdhG HCLeYge gPG hGddg cdg Mb hGdMeO ddg hMOg hHg CSJYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds